2017
DOI: 10.1111/1365-2664.12845
|View full text |Cite
|
Sign up to set email alerts
|

Reframing the evidence base for policy‐relevance to increase impact: a case study on forest fragmentation in the oil palm sector

Abstract: Summary It is necessary to improve knowledge exchange between scientists and decision‐makers so that scientific evidence can be readily accessed to inform policy. To maximise impact of scientific evidence in policy development, the scientific community should engage more fully with decision‐makers, building long‐term working relationships in order to identify and respond to ‘policy windows’ with science that is reframed for policy‐relevance. We illustrate the process and challenges using a case study in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Conservation of large tracts of high‐quality forest habitat is important for population persistence in human‐modified landscapes (e.g. see Edwards, Fisher, & Wilcove, ; Lucey et al, ), and so small HCVAs may be unable to support viable populations of forest‐dependent species unless they are well‐connected to other forested areas. However, our results suggest that if well positioned between large tracts of forest, smaller HCVAs may act as ‘stepping stones’ to facilitate movement across fragmented landscapes (Hodgson, Wallis, Krishna, & Cornell, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservation of large tracts of high‐quality forest habitat is important for population persistence in human‐modified landscapes (e.g. see Edwards, Fisher, & Wilcove, ; Lucey et al, ), and so small HCVAs may be unable to support viable populations of forest‐dependent species unless they are well‐connected to other forested areas. However, our results suggest that if well positioned between large tracts of forest, smaller HCVAs may act as ‘stepping stones’ to facilitate movement across fragmented landscapes (Hodgson, Wallis, Krishna, & Cornell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of all plantations we studied contained at least one HCVA patch large enough to support forest‐dependent species (i.e. with a core area >2 km 2 ) (Lucey et al, ), but these HCVAs may not contain good quality forest, which is needed for maintaining tropical biodiversity (Tawatao et al, ). Many of the HCVAs we studied had low forest cover, and we strongly recommend active management by plantation companies to improve forest extent and quality, such as enrichment planting (Yeong, Reynolds, & Hill, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the palm oil sector there are a variety of possible explanations for the current science-policy impasse. One broad explanation is the general disconnect between research, policy, and practice, which is common in academia where career advancement is focused toward academic outputs (Lucey et al, 2017). Hansen et al (2015) observed that the application and assimilation of research outputs from Malaysian universities into the palm oil industry has been minimal despite a significant rise in locally authored academic papers since the early 2000s.…”
Section: Improved Research Communication Strategiesmentioning
confidence: 99%
“…Following on from the emerging priorities as stated above, we recommend four action points to further develop the palm oil sustainability research agenda. These action points reflect a growing recognition in academia that research activities should have clearly defined societal benefits and impact as well as conventional academic outputs, such as journal publications (Lucey et al, 2017).…”
Section: Steps Toward a Sustainable Palm Oil Research Agendamentioning
confidence: 99%